Simultaneous EEG, fMRI, and Behavior in Typical Childhood Absence Seizures - Berman, Rachel (2010)
PURPOSE: Absence seizures cause transient impairment of consciousness. Typical absence seizures occur in children, and are accompanied by 3–4 Hz spike-wave discharges (SWD) on EEG. Prior EEG-fMRI studies of SWD have shown a network of cortical and subcortical changes during these electrical events. However, fMRI during typical childhood absence seizures with confirmed impaired consciousness has not been previously investigated. METHODS: We performed EEG-fMRI with simultaneous behavioral testing in 37 children with typical childhood absence epilepsy. Attentional vigilance was evaluated by a continuous performance task (CPT), and simpler motor performance was evaluated by a repetitive tapping task (RTT). RESULTS: SWD episodes were obtained during fMRI scanning from 9 patients among the 37 studied. fMRI signal increases during SWD were observed in the thalamus, frontal cortex, primary visual, auditory, somatosensory, and motor cortex, and fMRI decreases were seen in the lateral and medial parietal cortex, cingulate gyrus, and basal ganglia. Omission error rate (missed targets) with SWD during fMRI was 81% on CPT and 39% on RTT. For those seizure epochs during which CPT performance was impaired, fMRI changes were seen in cortical and subcortical structures typically involved in SWD, while minimal changes were observed for the few epochs during which performance was spared. DISCUSSION: These findings suggest that typical absence seizures involve a network of cortical-subcortical areas necessary for normal attention and primary information processing. Identification of this network may improve understanding of cognitive impairments in childhood absence epilepsy, and help guide development of new therapies for this disorder.